Nordic fascism
1 online resource (xviii, 224 pages).
Keywords: "Nordic Fascism is the first comprehensive history in English of fascism in the Nordic countries. Transnational cooperation between radical nationalists has especially been the case in Sweden, Denmark, Norway, and Finland, where fascism has not only developed through interdependent processes but through interactions between and beyond national boundaries, and where "racial relationship" has been a core argument. With chapters ranging from the inception of fascism in the interwar years up to the present day, this book offers the first fragments of an entangled history of Nordic fascism. It illuminates how The North occupies a special place in the fascist imagination, articulating ideas about the Nordic people resisting the supposed cultural degeneration, replacement, or annihilation of the white race. The authors map ideological exchange between fascist organisations in the Nordic countries and outline past and present attempts at pan-Nordic state building. This book will appeal to scholars of fascism and Nordic history, and readers interested in the general history of fascism"--